Survivorship of Meniscal Allograft Transplantation in an Athletic Patient Population. (May 2016) - Waterman, Brian R.; Rensing, Nicholas; Cameron, Kenneth L.; Owens, Brett D.; Pallis, Mark
Background: There are limited data evaluating the clinical outcomes of meniscal allograft transplantation (MAT) in physically active cohorts. Purpose: To determine the survivorship, complication rates, and functional outcomes of MAT in an active military population. Study Design: Case series; Level of evidence, 4. Methods: All military patients undergoing MAT between 2007 and 2013 were identified from the Military Health System. Previous/concomitant procedures, perioperative complications, reoperation rate, revision, and initiation of medical discharge for persistent knee disability were recorded. Univariate analysis was performed to identify associations between patient-based and surgical variables on selected endpoints. Results: A total of 230 MATs (227 patients; 228 knees) were identified; the mean patient age was 27.2 years (range, 18-46 years), and the cohort was predominately male (89%). Approximately half (51%) of the patients had undergone prior, nonmeniscal knee procedures. Medial MATs were performed in 160 (69%) cases, and isolated MATs were most common (60%). A total of 51 complications occurred in 46 (21.1%) patients, including a secondary tear or extrusion (9%). At a mean clinical follow-up of 2.14 years, 10 (4.4%) patients required secondary meniscal debridement, while 1 (0.4%) patient required revision MAT and 2 (0.9%) patients underwent total knee arthroplasty. After MAT, 50 (22%) patients underwent knee-related military discharge at a mean of 2.49 years postoperatively. Tobacco use ( P = .028) was associated with significantly increased risk of failure, and operation by fellowship-trained surgeons trended toward significance as a protective factor ( P = .078). Furthermore, high-volume surgeons (≥1 MAT/year; range, 9-35) had significantly reduced rates of failure ( P = .046). Conclusion: While reporting low reoperation and revision rates, this investigation indicates that 22% of patients with MAT were unable to return to military duty due to persistent knee limitations at short-term follow-up. Increased surgical experience may decrease rates of failure after MAT. Careful patient selection and referral to subspecialty-trained, higher-volume surgeons should be considered to optimize clinical outcomes after MAT.